2014
DOI: 10.1001/jamainternmed.2013.14458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Health Insurance and Facility Quality Improvement on Blood Pressure in Adults With Hypertension in Nigeria

Abstract: Background: Hypertension is a leading risk factor for death in sub-Saharan Africa. Quality treatment is often not available nor affordable. We assessed the effect of a voluntary health insurance program, including quality improvement of healthcare facilities, on blood pressure (BP) in hypertensive adults in rural Nigeria. Methods: We compared changes in outcomes from baseline (2009) to midline (2011) and endline (2013) between non-pregnant hypertensive adults in the insurance program area (PA) and a control ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 13 publications
0
63
0
Order By: Relevance
“…It is also noteworthy that not all documents identified from "policy sources" should be considered "policy documents, " under any conventional definition. Four citing "policy documents" in this sample were clearly standard peer-reviewed journal articles, but were categorized as policy documents citing the research articles by Moreno-Serra, 2012 (Hendriks et al, 2014) Lomas, Woodward, 2009(MacDicken, 2015, and Brazier, 2005 (Armstrong et al, 2013;Holmes et al, 2014). The quality of ascribed policy sources might potentially be an issue of concern, very much like that of predatory journals where argument can ensue as to the authenticity and credibility of a journal (Cartwright, 2016).…”
Section: Discussion Identification Of Relevant Policy Documents By Almentioning
confidence: 99%
“…It is also noteworthy that not all documents identified from "policy sources" should be considered "policy documents, " under any conventional definition. Four citing "policy documents" in this sample were clearly standard peer-reviewed journal articles, but were categorized as policy documents citing the research articles by Moreno-Serra, 2012 (Hendriks et al, 2014) Lomas, Woodward, 2009(MacDicken, 2015, and Brazier, 2005 (Armstrong et al, 2013;Holmes et al, 2014). The quality of ascribed policy sources might potentially be an issue of concern, very much like that of predatory journals where argument can ensue as to the authenticity and credibility of a journal (Cartwright, 2016).…”
Section: Discussion Identification Of Relevant Policy Documents By Almentioning
confidence: 99%
“…17,18 Some of the important patient-related reasons include awareness and understanding of the disease, 19 adherence to prescribed antihypertensive therapies and lifestyle changes, 20,21 access to medical care including drug affordability 22,23 and biology of the disease. 24 Healthcarerelated reasons include accepted standards and goals in hypertension treatment and control, physician education and familiarity with therapeutic options, antihypertensive regimen complexity, provider-patient interaction, and adequate patient follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in Nigeria and other countries in SSA has indicated that health system interventions such as health insurance coverage, organizational support to facilities and the training of health professionals can facilitate the access to and delivery of high quality CVD prevention care in primary care settings [8]- [14]. But even if high quality care is available, there is evidence that many patients fail to adhere to the recommended treatment and do not meet their treatment goals [15]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of studies on various strategies for improving the quality of primary hypertension care in high income countries concludes that organizational health system changes and patient education have the biggest impact on blood pressure (BP) outcomes [26]. Some recent primary care studies from Nigeria also demonstrate that organizational quality improvement interventions can lead to improved clinical outcomes in hypertensive patients [14] [27] [28]. However, to date little information is available about the impact of patient education on hypertension management in low resource communities in Nigeria or other countries in SSA.…”
Section: Introductionmentioning
confidence: 99%